A cross-sectional study on autologous: serum skin test in chronic urticaria in a tertiary care centre - D., Dharani; S., Krishnan; K., Manobalan (International Journal of Research in Dermatology, 2017)
Background: Urticaria persisting daily for more than six weeks is termed as chronic urticaria. A significant number of them have an autoimmune basis, where ASST is used for detection of chronic autoimmune urticaria (CAU). The aim and objective of the study was to determine the frequency of autoimmunity with ASST in chronic urticaria patients. Methods:This was a hospital based cross sectional study, 100 patients with chronic urticaria fulfilling the inclusion and exclusion criteria were enrolled in the study. Detailed history, physical examination and routine investigations were recorded and ASST was done for all patients. Results:Thirty seven (37%) out of 100 CU patients were ASST positive. Statistical analysis of the clinical variables did not show significant difference between ASST positive and negative patients except for dermographism and mean duration of the disease. Conclusions:ASST is a simple invivo clinical test for detection of basophil histamine releasing activity. Diagnosing CAU is important as these patients may need high doses of anti-histamines, systemic corticosteroids and/or immunomodulatory drugs. Autologous serum therapy itself has a therapeutic role in treatment of CAU patients.